Comparison of the effects of negative pressure wound therapy and negative pressure wound therapy with instillation on wound healing in a porcine model - Tingting, Sun; Xinyue, Feng; Tiantian, Yang; xiao, An; Rui, Li; Feng, Lin; Daohong, Liu; Zhirui, Li; Guoqi, Wang (Frontiers in Surgery, 2023)
Background Negative pressure wound therapy with instillation (NPWTi) is a novel method based on standard negative pressure wound therapy (NPWT). This study aimed to compare the effects of standard NPWT and NPWTi on bioburden and wound healing in a Staphylococcus aureus (S.aureus) infected porcine model. Methods Green fluorescent protein‑labeled S.aureus infected wounds were created on the back of porcine. Wounds were treated with NPWT or NPWT with instillation (saline). The tissue specimens were harvested on days 0 (12h after bacterial inoculation), 2, 4, 6, and 8 at the center of wound beds. Viable bacterial counts, laser scanning confocal microscopy, PCR, western blot and histological analysis were performed to assess virulence and wound healing. Results The bacterial count in the NPWTi group was lower than that of the NPWT group and the difference was statistically significant on day 2, day 4, day 6 and day 8 (P<0.05). The expression levels of agrA, Eap, Spa, and Hla genes of the NPWTi group were significantly lower than that of the NPWT group on day 8 (P<0.05). The bacterial invasion depth of the NPWTi group was significantly lower than that of the NPWT group on the day 2, day 4, day 6, and day 8 (P<0.05). Though NPWTi group showed a significant increased expression of bFGF and VEGF than that of NPWT group in the early time (P<0.05), NPWTi cannot lead to better histologic parameters than the NPWT group (P>0.05). Conclusion Our results demonstrated that NPWTi induced a better decrease in bacterial burden and virulence compared with standard NPWT. These advantages did not result in better histologic parameters on the porcine wound model.